Enhanced drought tolerance of Arabica coffee (Coffea arabica L.) by grafting method - Vu, Ngoc-Thang; Park, Jong-Man; Nguyen, Ngoc-Quat; Nguyen, Trong-Truong-Son; Kim, Il-Soep; Jang, Dong-Cheol (Penerbit Universiti Kebangsaan Malaysia, 2021)
The objective of this study was to evaluate grafting method to improve the drought tolerance of Coffea arabica. Using C. arabica species as scions, and C. robusta as rootstock, the grafted plant was compared with the non-grafted plant (C. arabica) under water deficit condition. The result shown that growth parameters such as plant height, leaf length, and leaf width of the grafted coffee plants were higher than those of the non-grafted. The leaf area, fresh and dry weight of plants were highly reduced in non-grafted coffee plants. The leaf chlorophyll content (SPAD) and chlorophyll fluorescence (Fv/Fm) values of the grafted and non-grafted coffee plants decreased significantly with increasing duration under water deficit condition. The SPAD and Fv/Fm values of the two coffee types were also increased significantly with increasing duration after re-watering. Compared to the non-grafted plants, higher values of SPAD, Fv/Fm and relative water content in the leaf were observed in the grafted coffee plants. Moreover, lower values of relative ion leakage were observed in the grafted coffee plants after three days of water withholding and one month after re-watering. On the other hand, the grafted coffee plants showed enhanced drought tolerance by reducing the percentages of wilting plant under water deficit condition, and increasing the recovery percentages after re-watering.